Analysis Of The Influence Of Corporate Size, Leverage , Price Earning Ratio (PER) And Return On Equity (ROE) On Company Value - Tegar Prasetya; Setyo Riyanto (Syntax Corporation Indonesia, 2020)
This study aimed to n use values the company can be determined by many factors, among which the size of the company, leverage, the price earnings ratio (PER) and Return On Equity (ROE) Firm size is considered able to influence the value of the company . the large size of the company shows that the company is developing so that investors will respond positively and the value of the company will increase. The relative market share shows the company's competitiveness is higher than its main competitors. Investors will respond positively so that the value of the company will increase. Companies that have total assets with large amounts or commonly referred to as large companies will get more attention from investors, creditors and other users of financial information compared to small companies. If the company has a large total assets, the management will be more flexible in using existing assets in the company. This ease in controlling assets will increase the value of the company. In the face of economic turmoil, usually a more sturdy company stands are large, although it does not rule out bankruptcy, so investors tend to like large-sized companies rather than small-sized companies.